Cognitive and Neurocognitive Potentials of GA’s Acts from the Scene of Language Origin - Złocka-Dąbrowska, Magdalena (Załącznik Kulturoznawczy, 2022)
The objective of the article is to look deeper into the GA’s scene of language origin in order to identify and discuss its acts together with the whole network of the scene’s components. Detailed studies of the nature of these acts and their fons et origo enable the author to unveil the successive levels justifying their presence and discover their cognitive and neurocognitive potentials. Eventually, they lead to intentionality without which it would be impossible for language to emerge and for humans to achieve a state of deferral of intra-human violence.